An improved control scheme for grid connected doubly fed induction generator considering wind-solar hybrid system. (May 2016) - Parida, Adikanda; Chatterjee, Debashis
Highlights: A grid connected DFIG based wind-solar hybrid generation scheme has been proposed. The DFIG control scheme has negligible sensitivity to machine parameter variations. A PV fed rotor side converter operates in isolation with the grid. The developed scheme ensures wider sub-synchronous operating speed range. The estimated energy cost justifies the economical viability for commercialization. Abstract: This paper proposes a wind-solar hybrid generation scheme, along with an improved control strategy for grid connected wind energy conversion system (WECS) considering parameter uncertainty. In the proposed scheme, a photo voltaic (PV) supplemented rotor power management scheme (RPMS) has been developed for doubly fed induction generator (DFIG) with stator connected to grid. The topology of RPMS is implemented in isolation with the grid during entire period of DFIG operation. The proposed scheme ensures an increased output power delivered to the grid during low wind speeds. The DFIG control scheme require accurate information for the rotor position and speed at all operating conditions, which is estimated in the proposed method without any significant dependency on machine parameters. The control strategy proposed in this paper is implemented with a 2.5 kW DFIG using dSPACE DS1104 module with PC interface, which produced satisfactory results.